Self-directed learning for optimizing sustainable language learning via mobile assisted language learning: a systematic review - Shalini Roy, S.; Gandhimathi, S. N. S. (Frontiers in Education, 2025)
Sustainability has become an essential factor in the field of education as the world evolves toward digitization. Technology is a valuable educational tool for sustainable development and it is rapidly adopted worldwide, leading to substantial educational innovations and findings. Technology such as Interactive Whiteboards, Learning Management Systems (LMS), and Mobile Assisted Language Learning (MALL), enhance self-directed learning among the learners. According to the goals of UNESCO, the 2030 Agenda for Sustainable Development Goal-4 (SDG4) focuses on quality education that endorses equity and equal opportunity for all. Mobile Learning is an educational method that can improve a teaching-learning context. However, limited studies have focused on utilizing MALL in the context of self-directed learning. The present study discusses the use of mobile applications for sustainable language learning. It provides a systematic review of the findings of 16 empirical studies published between 2019 and 2023 from Scopus and the Web of Science, based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020. The study analyzes the use of mobile apps for self-directed learning and highlights the importance of digital abilities in promoting lifelong learning. The result indicates the benefits of self-directed learning in promoting sustainable learning and discusses the potential of Mobile-Assisted Language Learning (MALL) in providing lifelong learning opportunities.